Studi Kasus Perencanaan Program Diet Dan Aktivitas Fisik Untuk Penderita Diabetes - Hafizah Anjeli Ramadhani; Jessy Ayu Angelia; Putri Fakhira Lubis; Febbry Zahro; Aulia Azahra Hafizh; Rizqy Aulia; Faliza Putri; Nurhidayah; Wulan Suci Ramadani; Debby Widytia; Adinda Naila Apsari; Muhammad Rafly; Khairunsyah; Dewi Agustina (PT. Padang Tekno Corp, 2026)
Diabetes mellitus merupakan penyakit kronis yang ditandai dengan peningkatan kadar gula darah akibat gangguan produksi atau kerja insulin. Penatalaksanaan diabetes tidak hanya bergantung pada terapi farmakologi, tetapi juga dipengaruhi oleh pengaturan pola makan dan aktivitas fisik. Penelitian ini bertujuan untuk menganalisis perencanaan serta implementasi program diet dan aktivitas fisik pada penderita diabetes mellitus melalui pendekatan studi kasus. Metode penelitian menggunakan pendekatan deskriptif dengan desain studi kasus pada satu pasien diabetes mellitus tipe 2. Intervensi yang diberikan berupa pengaturan diet berbasis prinsip 3J (jumlah, jenis, dan jadwal makan) serta aktivitas fisik rutin. Hasil penelitian menunjukkan adanya penurunan kadar gula darah dari 245 mg/dL menjadi 165 mg/dL dalam waktu 4 minggu. Penurunan ini menunjukkan bahwa intervensi yang diberikan efektif dalam membantu pengendalian kadar gula darah serta meningkatkan kepatuhan pasien terhadap pola hidup sehat. Hypertension is one of the most common noninfectious diseases that affects the elderly. Hypertension is also a leading cause of serious complications such as stroke, heart failure, and kidney disease. Non-pharmacological approaches such as the Mindfulness-Based Stress Reduction (MBSR) method have been proven effective in lowering blood pressure by reducing stress and increasing self-awareness. This study aims to determine the effect of relaxation therapy with the MBSR method on reducing blood pressure among elderly patients with hypertension. This research employed a quantitative approach with a quasi-experimental design. The design used was a pre-test post-test design. The sample consisted of 30 elderly selected using purposive sampling based on inclusion and exclusion criteria. The study was conducted from April 14th to June 3rd, 2025. The intervention given was an MBSR treatment program for two months, eight sessions, including mindfulness meditation, breathing exercises, and relaxation techniques. Blood pressure measurements were taken before and after the intervention. The data were analyzed using the paired t-test. The results showed a significant decrease in systolic blood pressure of P< 0.000 and diastolic blood pressure with P < 0.011 after intervention. The average reduction in systolic blood pressure was 5.13 mmHg, and in diastolic blood pressure was 4.63 mmHg. These findings indicate that the MBSR therapy is effective in helping elderly individuals manage hypertension through stress reduction and enhanced self-awareness